2011
DOI: 10.1142/s0218625x11014485
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Plasma Polymerized N,n,3,5 Tetramethylaniline Thin Films

Abstract: Plasma polymerized thin films of aluminium/thin film/aluminium configuration were deposited at room temperature by a parallel plate capacitively coupled glow discharge reactor using N,N,3,5 tetramethylaniline (TMA) as a precursor. The infrared spectroscopic analyses revealed that plasma polymerized TMA (PPTMA) films contained an aromatic ring structure with NC and CH side groups, presence of C = O was also evident. The differential thermal analysis and thermogravimetric analysis of PPTMA thin film was thermall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The dielectric data analyses showed the existence of distribution of relaxation time in these materials. Akther and Bhuiyan reported the dielectric constant and AC electrical conductivity of plasma‐polymerized N,N,3,5 tetramethylaniline (TMA) (PPTMA) thin films as functions of frequency (100 < f < 10 5 Hz) and temperature (300 < T < 450 K). They found that the electrical conductivity is more dependent on temperature in the low frequency region than in the high frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric data analyses showed the existence of distribution of relaxation time in these materials. Akther and Bhuiyan reported the dielectric constant and AC electrical conductivity of plasma‐polymerized N,N,3,5 tetramethylaniline (TMA) (PPTMA) thin films as functions of frequency (100 < f < 10 5 Hz) and temperature (300 < T < 450 K). They found that the electrical conductivity is more dependent on temperature in the low frequency region than in the high frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the increase in the charge mobility and the electrical conductivity were observed by the proper selection of metals with high work function as the electrode and by producing the films with low thickness. Akther and Bhuiyan [3,4] studied the current density-voltage (J-V) characteristics of plasma polymerized N,N,3,5-tetramethyaniline (PPTMA) thin films of different thicknesses at different temperatures with aluminium (Al) electrodes and reported that the films showed Ohmic behaviour at the lower voltage region and SCLC dominated by exponential trap distribution at the higher voltage region. The electronic conductivity of bilayer aniline-pyrrole thin films were studied by Morales et al [5].…”
Section: Introductionmentioning
confidence: 99%